Peningkatan Keaktifan dan Hasil Belajar Penjaskes Materi BelaDiri (Pencak Silat) Menggunakan Aplikasi Whatsapp Group Media Power Point Pada Siswa Kelas VI MI Nurul Islam Karangpaing, Grobogan Semester I Tahun Ajaran 2019/2020 - Kaola Kaola (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2023)
INCREASING ACTIVITY AND LEARNING OUTCOMES IN PEDIATRIC HEALTH MATERIAL BELADIRI (PENCAK SILAT) USING THE WHATSAPP GROUP APPLICATION WITH POWERPOINT MEDIA IN CLASS VI STUDENTS MI NURUL ISLAM KARANGPAING – GROBOGAN SEMESTER 1 OF THE 2019/2020 ACADEMIC YEAR.The aim of this research is to determine the increase in student learning outcomes after implementing the use of WhatsApp groups with PowerPoint media in learning Penjaskes and martial arts material (pencak silat). The type of research is classroom action research with the stages of each cycle consisting of planning, action, observation and reflection. The research subjects were 25 class VI students at MI Nurul Islam Karangpaing, Penawangan - Grobogan Semester 1 of the 2019/2020 academic year. Data collection techniques and tools use test and non-test techniques (observation and documentation). The data validation technique uses triangulation techniques. The data analysis method in this research uses qualitative data analysis. The research results showed that learning activity showed an increase from 28.00% or 7 students increased to 72.00% in the first cycle or as many as 18 students, and in the second cycle to 92.00% or as many as 23 students were declared complete in the last cycle and the increase the average initial study learning outcome was 58.00 to 67.20 in the first cycle, and in the second cycle it was 77.20 and the learning completeness increased from 5 students or 20.00% to 16 students or 64.00% and 22 students or 88.00% in the second cycle. From the results obtained above, it can be concluded that in the second cycle, the process of implementing learning improvements was declared successful and complete in the second cycle. From the explanation above, it can be concluded that using Whatsapp Group with Powerpoint Media can improve the process and student learning outcomes.Keywords: learning outcomes, whatsapp group, powerpoint mediaAbstrakTujuan dari penelitian ini yaitu untuk mengetahui peningkatan hasil belajar siswa setelah menerapkan penggunaan whatsapp group dengan media powerpoint dalam pembelajaran Penjaskes materi beladiri (pencak silat).Jenis penelitian adalah penelitian tindakan kelas dengan tahapan setiap siklus terdiri dari perencanaan, tindakan, pengamatan dan refleksi. Subjek penelitian adalah siswa kelas VI MI Nurul Islam Karangpaing,Penawangan - Grobogan Semester 1 Tahun Pelajaran 2019/2020 sebanyak 25 orang siswa. Teknik dan alat pengumpulan data menggunakan teknik tes dan non tes (observasi dan dokumentasi). Teknik validasi data menggunakan teknik triangulasi. Metode analisis data dalam penelitian ini menggunakan analisis data kualitatif. Hasil penelitian menunjukkan bahwakeaktifan belajar menunjukkan peningkatan dari 28,00% atau 7 siswa meningkat menjadi 72,00% pada siklus pertama atau sebanyak 18 siswa, dan pada siklus kedua menjadi 92,00% atau sebanyak 23 siswa dinyatakan tuntas pada siklus terakhir dan kenaikan rata-rata hasil belajar studi awal sebesar 58,00 menjadi 67,20 pada siklus pertama, dan pada siklus kedua menjadi 77,20serta peningkatan ketuntasan belajar dari 5 siswa atau 20,00% menjadi 16 siswa atau 64,00% dan 22 siswa atau 88,00% pada siklus kedua. Dari perolehan angka-angka di atas dapat disimpulan bahwa pada siklus kedua, proses pelaksanaan perbaikan pembelajaran dinyatakan berhasil dan tuntas pada siklus kedua. Dari penjelasan di atas dapat disimpulkan bahwa penggunaan Whatsapp Group dengan Media Powerpoint dapat meningkatkan proses, hasil belajar siswa.